Curious George and the puppies - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Vipah Interactive (Boston : Houghton Mifflin, 1998)
Curious George goes to the animal shelter where he accidentally lets all the dogs out of their cages and creates quite a ruckus.
Based on the character of Curious George created by Margret and H.A. Rey.
550
Accelerated Reader AR
Keywords: Monkeys -- Fiction; Animals -- Fiction